Toward an innovation radar for cultivated meat: exploring process technologies for cultivated meat and claims about their social impacts - Woelken, Lisa; Weckowska, Dagmara M.; Dreher, Carsten; Rauh, Cornelia (Frontiers in Sustainable Food Systems, 2024)
Introduction Cultivated meat has received growing attention since claims were made that cultivated meat can be produced more ethically and sustainably than the current meat production. However, there are still major challenges in the development of cell lines, scaffolding, growth media, and bioprocess, which need to be overcome to reach industrial production levels. Numerous technological innovations have been proposed to overcome these challenges but they have rarely been evaluated with regard to their social sustainability. Consequently, it remains unclear if and how cultivated meat would contribute towards creating inclusive food systems. Methods To bring more clarity, the study identifies different technological solutions that are used or developed for production of cultivated meat and identifies the positive and negative claims about the expected contributions of these technological solutions to social inclusion in food systems, using evidence from the literature review and 11 expert interviews. An innovation radar for cultivated meat is proposed to visualise the variety of technological innovations and the claims about their expected contributions to social sustainability. Results The technologies in the areas cell line development, scaffolding, growth media, and bioprocess are expected to have an impact on inclusion in consumption of cultivated meat. Some cell innovations are expected to raise cognitive barriers due to complex technologies that might be difficult for the consumer to understand. Cultural barriers are expected to be raised by cell innovation entailing genetic engineering and medium innovation using FBS or animal components, which is considered to harm animals. Further, regulatory barriers are expected in the EU if genetic modification is used in the production process, which concerns the areas cells, media, and scaffolding. The innovations for scaffolds are expected to mainly lower cost and cultural barriers since most technologies are already used in the food industry. Bioprocess innovations promise to lower cost barriers, however it must be considered, that most of the collected data for innovations in the bioprocess domain are based on assumptions. Discussion The study concludes that at this point in time, the most socially sustainable approach to cultivated meat production is not obvious. Under the current technological state of the art, it is not thinkable that production and consumption of cultivated meat could be socially inclusive. As it remains poorly understood if technologies for cultivated meat production could raise or lower barriers to inclusive consumption and production, further research is needed.